Study protocol: Fecal Microbiota Transplant combined with Atezolizumab/Bevacizumab in Patients with Hepatocellular Carcinoma who failed to achieve or maintain objective response to Atezolizumab/Bevacizumab – the FAB-HCC pilot study - Katharina Pomej; Adrian Frick; Bernhard Scheiner; Lorenz Balcar; Larissa Pajancic; Anton Klotz; Abelina Kreuter; Katharina Lampichler; Katharina Regnat; Kerstin Zinober; Michael Trauner; Dietmar Tamandl; et al. (PLoS ONE, 2025)
Background The gut microbiota is often altered in chronic liver diseases and hepatocellular carcinoma (HCC), and increasing evidence suggests that it may influence response to cancer immunotherapy. Strategies to modulate the gut microbiome (i.e., fecal microbiota transplant (FMT)) may help to improve efficacy of immune checkpoint inhibitors (ICIs) or even overcome resistance to ICIs. Here, we describe the design and rationale of FAB-HCC, a single-center, single-arm, phase II pilot study to assess safety, feasibility, and efficacy of FMT from patients with HCC who responded to PD-(L)1-based immunotherapy or from healthy donors to patients with HCC who failed to achieve or maintain a response to atezolizumab plus bevacizumab. Methods In this single-center, single-arm, phase II pilot study (ClinicalTrials.gov identifier: NCT05750030), we plan to include 12 patients with advanced HCC who failed to achieve or maintain a response to atezolizumab/bevacizumab. Patients will receive a single FMT via colonoscopy from donors with HCC who responded to PD-(L)1-based immunotherapy or from healthy individuals, followed by atezolizumab/bevacizumab every 3 weeks. The primary endpoint is safety, measured by incidence and severity of treatment-related adverse events. The main secondary endpoint is efficacy, as assessed by best radiological response according to RECISTv1.1 and mRECIST. Additional exploratory endpoints include data on the effect of FMT on recipient gut microbiota, as well as metagenomic analysis of stool samples, analyses of circulating immune cells and serum and stool proteomic, metabolomic and lipidomic signatures. Discussion The results of this study will help to define the potential of FMT as add-on intervention in the systemic treatment of advanced HCC, with the potential to improve efficacy of immunotherapy or even overcome resistance. Trial registration EudraCT Number: 2022-000234-42 Clinical trial registry & ID: ClinicalTrials.gov identifier: NCT05750030 (Registration date: 16.01.2023)